Digitizing the Values of Religious Character, Pancasila and Citizenship Education Through YouTube - Choirul Mahfud; Moh. Saifulloh; Niken Prasetyawati; Dyah S Y Agustin; Ni Wayan Suarmini; Enie Hendrajati; M. Charis Hidayat (MODELING: Jurnal Program Studi PGMI, 2021)
Digitalization is a keyword in the current era of the industrial revolution. In the future, there will likely continue to be a need for the Indonesian generation to obtain various information about the values of a religious character, Pancasila, and education in facing the challenges of the digital era. Therefore, this study focuses more on what and how digitalization efforts spread religious values, Pancasila, and education through YouTube social media carried out by anyone, both the government and the community. This research is based on data and documents with a qualitative descriptive method. The study results show many socialization and information efforts through YouTube that lecturers, teachers, and various parties carry out. The effect can be seen from the response and enthusiasm of the community. Also, to understand the message of the video on YouTube.